2006 Pervasive Health Conference and Workshops 2006
DOI: 10.1109/pcthealth.2006.361659
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Feasibility of PmEB: A Mobile Phone Application for Monitoring Real Time Caloric Balance

Abstract: inactivity are the main modifiable determinants of obesity Obesity is a major public health challenge with over [3]. From the National Weight Control Registry [25], 650 of U.S. adults either overweight or obese. Estimated Thubqiyomblepnscmiedwtter 1998 was about $78.5 billion [9], with half paid by icesn opttoa n ewr omncto Medicare and Medicaid, and the remainder paid by capabilities present an obvious opportunity for EMI private sources and out-of-pocket. Diet and physical apiton . Fis,teawy-are n laso natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 18 publications
(6 reference statements)
0
45
0
Order By: Relevance
“…Other applications such as PmEB [27,42] and BALANCE [26] take a different approach to journaling. They incorporate caloric information for a variety of foods and activity types, enabling users to more accurately monitor their daily caloric expenditure but at the cost of higher journaling effort.…”
Section: Design Space Of Mobile-phone Health Interventionsmentioning
confidence: 99%
“…Other applications such as PmEB [27,42] and BALANCE [26] take a different approach to journaling. They incorporate caloric information for a variety of foods and activity types, enabling users to more accurately monitor their daily caloric expenditure but at the cost of higher journaling effort.…”
Section: Design Space Of Mobile-phone Health Interventionsmentioning
confidence: 99%
“…An early example is PmEB, which demonstrated daily calorie budget feedback computed from a mobile food journal [9]. Siek et al studied journals for patients with chronic kidney disease, who found barcode and audio-based journals overwhelming [7].…”
Section: Related Workmentioning
confidence: 99%
“…For example, a mobile app developed for a Nokia platform, Wellness Diary, allows users to record health-related data such as weight, sleep, and physical activity, and receive feedback on input [14-16]. The Patient-Centered Assessment and Counseling Mobile Energy Balance (PmEB) app allows users to log food intake from a limited database of foods and track calorie balance [18]. Another app, UbiFit, was developed to promote change in physical activity [19].…”
Section: Introductionmentioning
confidence: 99%